Research on the relations between cognition and intelligent transformation of executive teams in small and medium-sized manufacturing enterprises. (April 2022) - Zhou, Jianlin; Lan, Shulin; Liu, Yi; Rong, Tengda; Huisingh, Donald
Abstract: Intelligent manufacturing is crucial to realize high-quality development and competitiveness improvement of the manufacturing industry. This study takes team cognition as the research perspective, seeks the antecedent variables and theoretical application scenarios of the intelligent transformation of small and medium-sized manufacturing enterprises, follows the theoretical paradigm of "cognition-behavior-effect" and contingency analysis logic of environmental factors to construct a relationship model that includes the cognitive complexity, cognitive flexibility, bricolage behavior and intelligent transformation of the executive team. An empirical research on the relationship of core variables are conducted based on the survey data from 195 small and medium-sized manufacturing companies. The results show that: bricolage behavior plays a partial mediating role between cognitive complexity and intelligent transformation and a complete mediating role between cognitive flexibility and intelligent transformation; cognitive complexity and cognitive flexibility positively regulate each other's relationship between the bricolage behavior and intelligent transformation. The research reveals an important question of "how small and medium-sized manufacturing executives' team cognition induces bricolage behavior and promotes intelligent transformation", with a view to further improving team cognition theory and bricolage theory, thus providing valuable suggestions on breaking resource constraints and pursuing transformation and upgrading for small and medium-sized manufacturing companies.